Inequality, politics and economic growth - Debajyoti Chakrabarty (Rutgers University, Department of Economics, 2000)
The paper studies the relationship between inequality and economic growth. This is done in a two sector model of endogenous growth with agents characterized by heterogeneity of factor endowments. The private sector consists of a large number of competitive firms who produce the only final good in the economy. This good is both consumable as well as accumulable. The government is seen to produce a productive factor interpreted as infrastructure. Infrastructure is both nonrival and accumulable. Infrastructural services flow into the production of infrastructural stocks as well as the final good. Capital used for infrastructural production is financed by the government by taxing capital income. The choice of the growth rate is determined by the tax rate on capital income. We study the choice of the economy's growth rate under a median voter democracy. The results show that inequality of the distribution of capital does not hamper growth.
Keywords: O41; 330; Endogenous growth; Neue Wachstumstheorie; Infrastruktur; Median Voter; Einkommensverteilung; Theorie